Identification of four plastid‐localized protein kinases. Issue 12 (7th June 2016) - Richter, Andreas S.; Gartmann, Hans; Fechler, Mona; Rödiger, Anja; Baginsky, Sacha; Grimm, Bernhard
Abstract : In chloroplasts, protein phosphorylation regulates important processes, including metabolism, photosynthesis, gene expression, and signaling. Because the hitherto known plastid protein kinases represent only a fraction of existing kinases, we aimed at the identification of novel plastid‐localized protein kinases that potentially phosphorylate enzymes of the tetrapyrrole biosynthesis (TBS) pathway. We screened publicly available databases for proteins annotated as putative protein kinase family proteins with predicted chloroplast localization. Additionally, we analyzed chloroplast fractions which were separated by sucrose density gradient centrifugation by mass spectrometry. We identified four new candidates for protein kinases, which were confirmed to be plastid localized by expression of GFP‐fusion proteins in tobacco leaves. A phosphorylation assay with the purified kinases confirmed the protein kinase activity for two of them. Abstract :